Morphological structures of elite karateka and their impact on technical and fighting efficiency - Katic, R.; Blazevic, S.; Krstulovic, S.; Mulic, R. (Collegium Antropologicum, 2005)
The aim of the study was to identify the morphological structures that determine achievement of top results in karate. The study included a sample of 85 karateka competing as senior category athletes within the Croatian Karate Society, aged 18-29 years. Sixteen morphological parameters were used; technical efficiency was assessed using 8 variables, i.e. evaluation of particular karate techniques, whereas fighting efficiency was estimated on the basis of results achieved at a number of contests. Factorial analysis of morphological space revealed the presence of four major factors: factor of muscle mass, followed by skeleton transverse dimensionality, factor of skeleton longitudinal dimensionality, factor of subcutaneous adipose tissue, and factor of shoulder width determining optimal trunk proportions (athlete type) in karateka. Regression analysis showed the isolated group of morphological factors to significantly determine both technical and fighting efficiency of karate athletes. Generally, skeleton longitudinality and muscle mass, followed by skeleton transverse dimensionality were found to exert favorable effects, and adipose tissue unfavorable effects according to both criteria. Also, each individual morphological factor influenced the performance of every karate technique applied. Adipose tissue had greatest unfavorable impact, whereas shoulder width and muscle mass had favorable impact on the performance of arm techniques (kicking). Considering performance of leg techniques, skeleton longitudinality had highest favorable impact, and adipose tissue greatest unfavorable impact. Of the techniques applied, combined karate kicks, i.e. jaku zuki-mawashi geri and kizame zuki-jaku zuki were found to be the best predictors of fighting efficiency.